Does racism affect a migrant's choice of destination? - Ruby Henry (Institute for the Study of Labor (IZA), 2009)
I explicitly introduce racial conflict and cultural attitudes on racial diversity as determinants of destination choice to test their continued relevance to African Americans. I construct several measures of racial intolerance towards African Americans using hate crime activity and the feelings of white Americans about race extracted from a national social attitudes survey. Recognizing that African American migration may actually spawn hate crimes against them, I use a control function method with assaults on white police officers and hate crimes against Jews as instruments to correct for potential endogeneity. The results show that the probability of African American migrants choosing a city is significantly reduced by per capita hate crimes against them, the level of race-based crimes against them, by racially intolerant attitudes held by whites, and by poor evolution in whites' feelings about racial diversity - all regardless of the region in which a city is located. Also striking is the previously undocumented divide among African Americans with respect to region, after controlling for racial intolerance. Those starting in the North exhibit an extreme distaste for the South at the margin, which contrasts sharply to the extreme taste for the South displayed by African Americans originating in the South.
Keywords: J15; J61; R23; C25; 330; Racial violence; discrimination; migration; conditional logit; Ethnische Diskriminierung; Migranten; Afrikaner; Wohnstandort; USA